Membranas: a experiência na gravura e seus processos - Liliana Lobo Ferreira (2006)
Membrane: prints experience and process. This art research develops a stratified view about what print brings up while image formation and its process. What moves print returns as a thinking movement, with the same plasticity, fluxes and consistence of prints process.When the matrix is involved, an image is produced, followed by another matrix and by another image composing layers throughout impressions. Print as a moving body is powerful: born, reborn, form, deform making membranes which become worlds thought, establishing connection with this worlds conscience through its contagious force, impregnating us and conceived art.